Physicochemical parameters of the water of the Salitre ponds influencing the sexual maturity of Trichomycterus punctulatus (Valenciennes, 1846), in the Jequetepeque Valley, Cajamarca-Peru. (LACCEI, 2024)
This research work is carried out in the Centro Poblado El Salitre, district of Tantarica, province of Contumazá department of Cajamarca- Peru. The research derives from a thesis work of the National University of Cajamarca, with the data that were obtained from the mining canon project "Obtaining seed by induced reproduction of Trichomycterus punctulatus Valenciennes 1846 (Life), and intensive cultivation in the Jequetepeque valley, Cajamarca, Peru". The work is based on determining the correlation of the physicochemical parameters of pond water during the sexual maturity of T. punctulatus. In which all the data of interest for the research work that were obtained from the database of the mining canon project were recorded. Obtaining as results that between the months of October 2020 to April 2021, 99 specimens of T. punctulatus, life had been sampled, of which 77 were females and 22 males, with an average height of 17.55 cm and an average weight of 45.75 g. In addition, the highest gonadosomatic index in females was obtained in January with an average of 19.39%. Also, most of the life specimens were in the mature and gravid stage and the correlation that could be determined by the Rho Spearman test, between the stage of sexual maturity of T. punctulatus with the temperature and pH of the water was significant direct (p0.05), and the correlation with the dissolved o0xigen and the conductivity of the water was inverse but not significant (p> 0.05). On the other hand, during the mature stage the weight of the gonad presented a significant inverse correlation (p0.05) with temperature, conductivity and dissolved oxygen and during the gravid stage the weight of the gonad presented an inverse and significant relationship (p0.01) with conductivity and pH.